Why do the econometric-based studies on the effect of warming on agriculture disagree? A meta-analysis. (8th December 2017) - Huang, Kaixing; Sim, Nicholas
Abstract: Having robust estimates of how global warming affects agriculture is important to policymakers, but the existing econometric-based studies have been at odds on what this effect might be. This article conducts a meta-analysis based on 130 primary econometric-based studies to better understand the conflict among the existing estimates on the effect of warming on agriculture. We find that differences in the latitude of the study sample, the temperature measure that was used, and the econometric approach that was applied can explain why the primary studies disagree. We also have evidence of publication bias where negative effects of warming are more likely to be published than positive effects are. Finally, we find that the disagreement could be reduced if the studies account for adaptation by using a yearly temperature measure and the hedonic approach.